Intimidation among coetaneans (bullying): empathy and social maladjustmen in participants of bullying - García Ampudia, Lupe (2011)
Intimidation among coetaneans inside educational centres constitutes a problem in our educational reality, the participants are aggressors, victims and spectators. The objective of this research is to analyse, describe and establish the relationship between empathy and school maladjustment in participants of intimidation among coetaneans and to compare the variables of empathy, social maladjustment according to genre and school grade. The sample was represented by 820 students from four public high schools in Lima Metropolitan; the instruments used for this research were the Interpersonal Reactivity Index (IRI,Davis 1980) in its Spanish versión (Mestre,V.,Frias,M.y Samper,P. 2004), a questionnaire of school maladjustment which was adapted from the Questionnaire of Intimidation  and Mistreatment among coetaneans Insebull (Avilés,J. y Elices,J. 2007) and the self-designation of the participants as aggressors, victims and spectators. The main results establish differences of genre in all the scales of empathy and differences of school grade in scales corresponding to the cognitive dimension of empathy; Differences of genre and school grade in school maladjustment were not found. In regard to empathy and the position of the aggressor, victim and spectator, differences in the scale of taking perspectives, personal discomfort and school maladjustment were found.